Характеристика оселищ рідкісних афілофороїдних грибів Національного природного парку «Гомільшанські ліси» (Україна) - Якунькін, Яків Дмитрович; Згонник, Микола Олексійович; Дмитрохін, Олег Андрійович; Yakunkin Ya.; Zghonnyk M.; Dmytrokhin O. (Львівський національний університет імені Івана Франка, 2021)
During our study localities of three rare fungal species: Polyporus umbellatus (Pers.) Fr., Buglossoporus quercinus (Schrad.) Kotl. & Pouzar and Hericium coralloides (Scop.) Pers. were studied. Around the places of basidiomata detection, test plots with an area of 500 square meters were laid. Dendrometric characteristics and deadwood stocks in these test plots were assessed. Based on the data about the substrate preferences of the model species, a prediction of their survival in those microhabitats has been made.
Characteristics of habitats of rare Aphyllophoroid fungi in the National Nature Park "Homilshanski lisy" (Ukraine)
Keywords: rare fungi; natural old growth forests; microhabitats; theats; prognosis